الأمثال القرآنية وأثرها في الدعوة إلى الله - دردوري, كريمة (University of Eloued جامعة الوادي, 2017)
الدعوة إلى الله تعالى، من أجل شرائع الإسلام الحنيف الذي بعث به لبنة التمام، ومسك الختام، وهذه الدعوة ضاربة بجذورها في عمق التاريخ البشري .وتكمن أهميتها في نشر العلم النافع بين الناس والثبات على الخلق الكريم الذي دعانا إليه الحبيب المصطفى عليه السلام ،وأن من بركة الدعوة إلى الله ما يكون لها أثار طيبة من رجوع إلى الحق والعمل به ،وإنتشار الخير ،وإندحار الشر وأهله وأن شعار هذه الأمة هو الدعوة إلى الله فقد كانت تهدف إلى محبة الخالق والتدبر في ملكوت السموات والأرض ،ونشر الخير والسلام والأمن والأمان ..... لما لها من مكانة وأهمية كبيرة في القرآن كما اهتم بها القرآن لأنها تعد مرجع ملئ بالعبر والدروس والوصول إلى نتيجة يرجى أن تكون عونا لكل داعية من خلال الاقتداء والتعلم من الأمثال القرآنية The call to God, for the laws of Islam, which was sent by the Bloc of the universe, and the conclusion of the conclusion, and this call rooted in the depth of human history. It is important in the dissemination of useful science among people And that the blessing of the call to God has no good effects from the return to the right and work, and the spread of good, and the desecration of evil and its people and that the motto of this nation is the call to God was aimed at the love of the Creator And in the Kingdom of the heavens and the earth, and the dissemination of good and peace and security and safety ..... Because of its importance and importance in the Koran as the Koran is concerned because it is a reference full of lessons and lessons and reach a result Please be helpful to each advocate through the practice and learning from the Koranic proverbs
مذكرة ماستر تخصص دعوة واعلام
Keywords: القرآن الكريم- الدعوة الى الله – الامثال القرآنية – العمومية; Quran - Call to God - Quranic Proverbs - General